HUBUNGAN PENGETAHUAN IBU TENTANG PERALATAN RUMAH TANGGA BERBAHAN MELAMIN TERHADAP PEMANFAATANNYA (Studi Analitik Di RW 03 RT 01 Dusun Gadungan Desa Nobo Kecamatan Puncu Kabupaten Kediri) - Mubaidah, Siti; Lukiana, Candra (Jurnal AKP, 2011)
Melamine is a substance causing cancer, losing function of reproduction organs, renal failure if its used in long term using. If its used in short term using, melamine can cause vomiting and diarhea. The purpose of this study to determine the relationship of mother knowledge about household appliances made of melamine to their benefit.The research design is analitic cross sectional with population Hamlet Village Gadungan Nobo RT 01 RW 03. Sampling of research used is consecutive sampling with 20 samples of mothers who live in Orchard Village Gadungan Nobo RT 01 RW 03. Analysis of data used by cross tabulation.Results from this study showed 18 respondents who have good knowledge. 4 respondents from 18 respondents have good knowledge using and 14 the other have enough knowledge using. From the results obtained by rank correlation spearmean significant value (Ï) 0,024 with an error rate (Î±) 0,05. Thus Ï < Î± then H0 refused and H1 accepted. This shows that there is a relationship between maternal knowledge about household appliances made from melamine to their benefit.Â In this study there is a relationship of household appliances made of melamine to their benefit is modereate.